Merendino Resection vs. Transhiatal Gastric Conduit After Resection of the Cardia and the Gastroesophageal Junction. Issue 2 (February 2022) - Eichelmann, Ann-Kathrin; Nikitina, Milana; Bahde, Ralf; Mardin, Wolf A.; Slepecka, Patrycja; Kebschull, Linus; Senninger, Norbert; Pascher, Andreas; Palmes, Daniel
Background: Reconstruction after combined cardia resection and removal of the gastroesophageal junction can be carried out by the Merendino procedure or via a gastric conduit. This study compares postoperative complications and quality of life for both approaches. Methods: All patients who underwent Merendino or gastric conduit reconstruction from 2011-2017 were included. Both groups were investigated regarding postoperative length of stay, complications, and gastrointestinal quality of life. Results: 45 patients were identified, of which, 39 remained for analysis: 22 patients in the Merendino group and 17 patients in the gastric conduit group. The median age of patients in the gastric conduit group (71 (53-92) years) was significantly higher than in the Merendino group (58 (19-75) years), P = .0002. Hospital stay was significantly longer in the gastric conduit group (35.9 (11-82) days vs. 18.2 (7-43) days, P = .0299) and incidence of anastomotic leakage was higher (24% vs. 9%, P = .0171). General incidence of complications (Clavien-Dindo) did not vary ( P = .1694). However, grade 5 complications only occurred in the Merendino group (n = 1). Evaluation of long-term outcome and quality of life showed dysphagia to only have occurred in the Merendino group (n = 3, 14%). Discussion: Both approaches have advantages and disadvantages: The Merendino procedure showed reduced incidence of anastomotic leakage and shorter hospital stay but was associated with a higher in-hospital mortality rate. Discrepancies in subgroup populations as well as small patient numbers limit the interpretation of the findings. This study does however provide a first comparison of these surgical approaches and may serve as a basis for further investigation.